Upgrading and repairing PCs - Mueller, Scott (Indianapolis, IN : Que, 1995)
Upgrading and Repairing PCs, Fifth Edition, is the most comprehensive PC support reference available. Discover the best way to assess your system, install hardware, and troubleshoot problems. Learn about the latest state-of-the-art motherboards, processors, memory, and disk drives. This book addresses all PC-compatible systems, from notebooks to towers, as well as Windows 95 and the new Plug and Play standard - providing the most complete and up-to-date technical reference available. This book contains everything you need to know. You'll find detailed information and specifications for every component in your PC, including major peripherals. Special sections detail system capabilities and upgrade options, and troubleshooting tips help you identify and solve problems.
Includes index.
Systems requirements for accompanying computer disc:IBM PC or compatible system; Microsoft Windows.
oif 18/02/15
Loan
Keywords: Microcomputers -- Equipment and supplies; Microcomputers -- Maintenance and repair; Microcomputers -- Upgrading